A review of necrotising enterocolitis in very low birth weight babies in a tertiary hospital in Johannesburg - Sandra Motsisim; Daynia Elizabeth Ballot (Wolters Kluwer Medknow Publications, 2023)
Introduction: Necrotising enterocolitis (NEC) is the most common gastrointestinal complication in pre-mature infants. There are risk factors and modifying factors that have been identified and studied over the years, but not many studies have been conducted in middle-income countries. Aims and Objectives: This study aimed to describe the maternal, obstetric and neonatal characteristics in very low birth weight (VLBW) babies with NEC in a tertiary neonatal unit in South Africa. The survival to hospital discharge in VLBW babies with NEC was also determined. Materials and Methods: This study was a retrospective, cross-sectional, observational study of VLBW babies admitted to a tertiary neonatal unit between January 2013 and December 2017. The population comprised babies <1500 g and <37 weeks gestation. Maternal and neonatal risk factors of NEC were compared in infants with and without NEC. Results: In this study, 173 out of 2111 (8%) babies were diagnosed with NEC. HIV exposure, late-onset sepsis, respiratory support after initial resuscitation, administration of surfactant and blood transfusion were associated with NEC. Surgery was performed in 48/173 (27.7%) of babies with NEC. The mortality rate in babies with NEC was 49.1%. Death in babies with NEC was associated with surgery for NEC (P = 0.01), mechanical ventilation (P < 0.001) and late-onset sepsis (P = 0.018). Conclusion: Risk factors for NEC in our population are similar to other countries, with some variations such as HIV. Even though some prevention measures have been implemented, the mortality rate remains high.